THE INFLUENCE OF RELIGIOSITY AND HALAL AWARENESS ON THE PURCHASE INTENTION OF THE MUSLIM Z GENERATION IN WARDAH COSMETIC PRODUCTS (CASE STUDY AT KAZANA COSMETICS STORE) - Adelia Winanda; Ahmad Rafiki; Yuni Syahputri (SEAN Institute, 2023)
The topic of this study is